Pengaruh Penerapan Prinsip Good Corporate Governance Terhadap Kinerja Non Keuangan Pada Perum Bulog Sub Divre Semarang - Adela Rahma Putri; Sartika Wulandari (Akuntansi dan Manajemen, 2021)
Non-financial performance is performance that shows a growth company. Companies can find out the success rate of their company by using non-financial performance analysis. The purpose of this study is to examine whether there is an influence between transparancy, accountability, responsibility, independency and fairness on the company’s non-financial performance. The method used is non-probability sampling with purposive sampling method and obtained through a questionnaire with a number of respondents as many as 40. Based on the results of hypothesis testing, it shows that the hypothesis of transparancy and accountability has no significant effect on non-financial performance, while the hypothesis of responsibility, independency and fairness have a positive and significant effect on non-financial performance. Keywords: Non-financial performance, Transparancy, Accountability, Responsibility, Independency, Fairness